From Arabism to Inclusivism: Reorientation of Al-Irsyad's Educational Patterns in East Java, 1919-1984 - Dzhilaal Al Baqi Bahalwan (UIN Sumatera Utara Medan, 2022)
This article aims to provide a description and analysis of the changes in the style of education of Al-Irsyad organization in East Java from 1919 to 1984. The style of Arabism that is closely related to Al-Irsyad is gradually fading. This study uses historical research methods with the primary sources used being official organization documents and direct witnesses. The results of this study indicate that Al-Irsyad education in East Java had a shifting in style, from bolder Arabism to tending to be normative and inclusive. This shifting was caused by the formalization of the government's education curriculum, the needs of the times, and demands for adjustment to the local indigenous people. One of the main consequences of this shift was the decline in the number of educators and scholars from Al-Irsyad’s education.